Erratum: SC83288 is a clinical development candidate for the treatment of severe malaria - Stefano Pegoraro; Maëlle Duffey; Thomas D. Otto; Yulin Wang; Roman Rösemann; Roland Baumgartner; Stefanie K. Fehler; Leonardo Lucantoni; Vicky M. Avery; Alicia Moreno-Sabater; Dominique Mazier; Henri J. Vial; et al. (Nature Communications, 2017)
Nature Communications 8 Article number:14193 (2017); Published 31 January 2017; Updated 6 Apr 2017 This Article contains errors in Figs. 1 and 8 that were introduced during the production process. The compound on the lower right side of Fig. 1 is labelled incorrectly and should be labelled ‘SC83288’. The correct version of Fig.